2007
DOI: 10.1016/j.jhep.2007.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Early ribavirin pharmacokinetics, HCV RNA and alanine aminotransferase kinetics in HIV/HCV co-infected patients during treatment with pegylated interferon and ribavirin

Abstract: Background-We evaluated whether early ribavirin pharmacokinetics differ comparing hepatitis C/human immunodeficiency virus coinfected sustained virological responders and nonresponders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Jessner et al [31] showed that in patients who did not have at least a one log drop in viral load at day one of therapy, 100% were non-responders. While the standard of care has changed since these initial reports, making it hard to utilize the exact criteria found in these studies, it is interesting to note that numerous subsequent studies have shown results allowing for increasingly early prediction of treatment non-response, e.g, [32]. In a recent study, Sherman et al [33] found that in HCV/HIV-coinfected patients treated with PEG-IFN+RBV, IFN+RBV effectiveness ≥90% was associated (p=0.02) with viral clearance.…”
Section: First-phase Hcv Rna Decline During Interferon-α Based Therapymentioning
confidence: 99%
“…Jessner et al [31] showed that in patients who did not have at least a one log drop in viral load at day one of therapy, 100% were non-responders. While the standard of care has changed since these initial reports, making it hard to utilize the exact criteria found in these studies, it is interesting to note that numerous subsequent studies have shown results allowing for increasingly early prediction of treatment non-response, e.g, [32]. In a recent study, Sherman et al [33] found that in HCV/HIV-coinfected patients treated with PEG-IFN+RBV, IFN+RBV effectiveness ≥90% was associated (p=0.02) with viral clearance.…”
Section: First-phase Hcv Rna Decline During Interferon-α Based Therapymentioning
confidence: 99%
“…After that, the plasma or serum samples can be stored at -20°C. Another assumption recently made by Dahari et al is that measuring intra-erythrocyte ribavirin concentrations could be a more relevant approach than measuring plasma levels, based on the assumption that intra-erythrocyte ribavirin accumulation early on during treatment would be higher in patients more likely to achieve SVR [46]. However, the irreversible intra-erythrocyte accumulation of RTP is probably not representative of the drug turnover in other target cells, such as hepatocytes, where ribavirin activation into triphosphate metabolites is reversible.…”
Section: "Several Analytical Methods Have Been Developedmentioning
confidence: 99%
“…In the clinical study reported by Dahari et al in this issue of the Journal, the authors analysed the early pharmacokinetics of ribavirin in HIV/HCV co-infected patients during treatment with pegylated interferon and ribavirin together with HCV plasma clearance and improvement of liver cytolytic enzymes activity in order to evaluate differences between responder and non responder co-infected patients to combination therapy for HCV infection [6].…”
Section: See Article Pages 23-30mentioning
confidence: 99%